Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah Dasar - Aziz, Asep Abdul; Hidayatullah, Ajat Syarif; Ruswandi, Uus; Arifin, Bambang Samsul (Jurnal Penelitian Pendidikan Islam, 2021)
This article aims to reveal the concept of Islamic religious education learning in elementary schools.In the development of primary school age children have their own characteristics, the ability to think of elementary school age children develop gradually. It needs to be understood wisely to be able to deliver successful educational goals. This research adopts a descriptive qualitative approach with library research methods. The results showed that Islamic religious education in elementary school is quite unique, if in the past the mind of the child is still imaginative and egocentric then at this time the child's mind develops towards concrete, rational and objective thinking. The scope of islamic religious education study is the Qur'an, religion, morals, fiqh /worship, and islamic cultural history. The method of education that can be applied refers to the Qurani method namely amstal method, qishah method, ibrah mauidzah method, hiwar jadali method, uswah hasanah method, and targhib tarhib method. Meanwhile, Islamic education can be carried out verbally or non verbally, writing or non-writing aimed at measuring intellectual komptensi, social competence, social competence and spiritual competence. Thus, Islamic religious education is expected to produce people who always strive to perfect faith, piety, and morality, and actively build Islamic civilization.